Fixed Compounds Containing 145 the Names of Warfare Tools in a Motivation Situation - Połowniak-Wawrzonek, Dorota (Respectus Philologicus, 2006)
The present article comprises characteristics of fixed compounds where one component is a name of warfare tools in a motivation situation. Fixed compounds, which function in military language, are distinguished there. Only certain compounds (mostly the most general) from specialised language (specifying detailed meanings) pass to the common. general language. A lot of compounds comprising the names of warfare tools were fixed already in military texts. There were registered metonymic processes and metaphorical changes. The domain of destination comprises compounds, which are formed with elements of semantic changes and certain pragmatic conditions, which can influence future metaphorisation processes and use of the compounds in texts. There were also registered compounds in military texts as loose compounds and they were ascribed to phraseologization in non-military texts.